Magnetic Resonance Imaging for Breast Cancer Classification Using Convolutional Neural Networks - Mahiruna, Adiyah; Destriana, Rachmat; Riansyah, Rahmat (Journal of Applied Informatics and Computing, 2025)
Breast cancer remains a leading cause of mortality among women worldwide, emphasizing the urgent need for accurate diagnostic methods. This research addresses the challenges of early detection by leveraging Convolutional Neural Networks (CNNs) for the classification of Magnetic Resonance Imaging (MRI) data. Using a publicly available Kaggle dataset consisting of 54,676 MRI images categorized into "Normal" and "Cancer" classes, the dataset was split into 80% for training and 20% for validation. A modified CNN architecture was developed, incorporating optimized layers and hyperparameters, such as the ADAM optimizer, a learning rate of 0.0001, and a mini-batch size of 128. The proposed model achieved exceptional performance, with an accuracy of 99.72%, precision and recall of 99.98% and 99.97%, respectively, and an F1-score of 99.98%, as evaluated through a confusion matrix. These results demonstrate the model’s robustness in distinguishing between healthy and cancerous tissues, providing a reliable and efficient diagnostic tool. This study highlights the potential of CNNs to improve diagnostic precision in medical imaging, aiding clinicians and advancing AI applications in healthcare.